2018
DOI: 10.3390/ijms19072120
|View full text |Cite
|
Sign up to set email alerts
|

Non-Coding RNAs in Endometrial Physiopathology

Abstract: The Human Genome Project led to the discovery that about 80% of our DNA is transcribed in RNA molecules. Only 2% of the human genome is translated into proteins, the rest mostly produces molecules called non-coding RNAs, which are a heterogeneous class of RNAs involved in different steps of gene regulation. They have been classified, according to their length, into small non-coding RNAs and long non-coding RNAs, or to their function, into housekeeping non-coding RNAs and regulatory non-coding RNAs. Their invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(71 citation statements)
references
References 190 publications
(211 reference statements)
2
65
0
Order By: Relevance
“…Intriguingly, results generated by Ingenuity Pathway Analysis software revealed that E2-regulated genes were enriched with terms related to cancer diseases. Indeed, endometrioid type endometrial cancers (EEC), which represent around 70-80% of all endometrial cancers, are associated with increasing estrogen levels that, in turn are responsible for impaired control of cell proliferation (reviewed in [84]). Using the Hec-1A endometrial cancer cell line it has been demonstrated that diacylglycerol kinase alpha (DGKA) activity is required for E2-stimulated cell proliferation, as using DGKA inhibitors resulted in E2-stimulated proliferation and growth of Hec-1A cells [85].…”
Section: Involvement Of Estrogen Signaling In Processes Related To Cementioning
confidence: 99%
“…Intriguingly, results generated by Ingenuity Pathway Analysis software revealed that E2-regulated genes were enriched with terms related to cancer diseases. Indeed, endometrioid type endometrial cancers (EEC), which represent around 70-80% of all endometrial cancers, are associated with increasing estrogen levels that, in turn are responsible for impaired control of cell proliferation (reviewed in [84]). Using the Hec-1A endometrial cancer cell line it has been demonstrated that diacylglycerol kinase alpha (DGKA) activity is required for E2-stimulated cell proliferation, as using DGKA inhibitors resulted in E2-stimulated proliferation and growth of Hec-1A cells [85].…”
Section: Involvement Of Estrogen Signaling In Processes Related To Cementioning
confidence: 99%
“…We encourage the scientific community consider the aforementioned tissues to compliment the conclusions of this systematic review. For example, an interesting study by Ferlita et al discussed the function of non-coding RNAs (including miRNAs) in endometrial physiology, analyzing their role in endometrial pathologies, such as endometrial cancer, endometriosis, and chronic endometritis [53]. Moreover, mounting evidence suggests that epigenetic changes may play a vital role in both placental-induced diseases, such as pre-eclampsia, and intrauterine growth restriction [54,55].…”
Section: Looking Beyond the Present Systematic Reviewmentioning
confidence: 99%
“…Another inhibitor, estradiol-3-O-sufamate (E2MATE) used on human endometrial explants and in a mouse model of endometriosis has shown some promising results [106]. but have yet to be tested as a treatment for women with EC or endometriosis.…”
Section: Intracrinology and Metabolismmentioning
confidence: 99%